Phylogenetic variations in a novel family of hyperstable apple snail egg proteins: insights into structural stability and functional trends - Pasquevich, María Yanina (2024)
The relationship between protein stability and functional evolution is little explored in proteins purified from natural sources. Here, we investigated a novel family of egg proteins (Perivitellin-1, PV1) from Pomacea snails. Their remarkable stability and clade-related functions in most derived clades (Canaliculata and Bridgesii) make them excellent candidates for exploring this issue. To that aim, we studied PV1 (PpaPV1) from the most basal lineage, Flagellata. PpaPV1 displays unparalleled structural and kinetic stability, surpassing PV1s from derived clades, ranking among the most hyperstable proteins documented in nature. Its spectral features contribute to a pale egg coloration, exhibiting a milder glycan binding lectin activity with a narrower specificity than PV1s from the closely related Bridgesii clade. These findings provide evidence for substantial structural and functional changes throughout the genus´ PV1 evolution. We observed that structural and kinetic stability decreased in a clade-related fashion and was associated with large variations in defensive traits. For instance, pale PpaPV1 lectin turns potent in the Bridgesii clade, adversely affecting gut morphology, while giving rise to brightly colored PV1s providing eggs with a conspicuous, probably warning signal in the Canaliculata clade. This work provides a comprehensive comparative analysis of PV1s from various apple snail species within a phylogenetic framework, offering insights into the interplay among their structural features, stability profiles and functional roles. More broadly, our work provides one of the first examples from natural evolution showing the crucial link among protein structure, stability and evolution of new functions.